Fantastic Four. Full circle - Ross, Alex, 1970-; Ross, Alex, 1970-; Lee, Stan, 1922-2018; Kirby, Jack (Abrams Comic Art, 2022)
It's a rainy night in Manhattan and not a creature is stirring except for ... Ben Grimm. When an intruder suddenly appears inside the Baxter Building, the Fantastic Four -- Mister Fantastic (Reed Richards), the Invisible Woman (Susan Storm Richards), the Human Torch (Johnny Storm), and the Thing (Ben Grimm) -- find themselves surrounded by a swarm of invading parasites. These carrion creatures composed of Negative Energy come to Earth using a human host as a delivery system. The Fantastic Four have no choice but to journey into the Negative Zone, an alien universe composed entirely of anti-matter, risking not just their own lives but the fate of the cosmos! Fantastic Four: Full Circle is the first longform work written and illustrated by acclaimed artist Alex Ross, who revisits a classic Stan Lee-Jack Kirby story from the 1960s and introduces the storyline for a new generation of readers.